Application of Poka-Yoke and Kanban Methods to Improve Shoe Production Efficiency At PT.xyz - Twonando, Ficky; Permadi, Rama; Hakim, Achmad Luqman; Arnanda, Halif Tri; Ardiansah, Arki (Indonesian Journal of Engineering and Technological Innovation, 2025)
This study aims to examine how the application of the Poka-Yoke and Kanban methods can improve production process efficiency at PT. XYZ, a hypothetical shoe company simulated using dummy data. In this simulation, daily production capacity is set at 1,000 pairs of shoes with an initial defect rate of 5% and a Work in Process (WIP) quantity of 1,000 pairs. The results show that the implementation of Poka-Yoke, which serves to prevent human error during the production process, successfully reduced the defect rate to only 0.1% and saved approximately Rp 73,500,000 per month. Meanwhile, the implementation of Kanban, which focuses on controlling material flow and inventory efficiency, was able to reduce the number of WIP by 70% and generate savings of around Rp 210,000,000 per month. Financial analysis shows a Return on Investment (ROI) of 782% for Poka-Yoke and 4,940% for Kanban, meaning that both methods are highly profitable. When applied simultaneously, they also increase the number of finished products (throughput) by 18.75%. Overall, this study demonstrates that the combination of Poka-Yoke and Kanban can be an effective strategy for reducing waste, minimizing product defects, and improving productivity in the modern shoe industry.